2016
DOI: 10.15252/embj.201592701
|View full text |Cite
|
Sign up to set email alerts
|

How to make a synaptic ribbon: RIBEYE deletion abolishes ribbons in retinal synapses and disrupts neurotransmitter release

Abstract: Synaptic ribbons are large proteinaceous scaffolds at the active zone of ribbon synapses that are specialized for rapid sustained synaptic vesicles exocytosis. A single ribbon-specific protein is known, RIBEYE, suggesting that ribbons may be constructed from RIBEYE protein. RIBEYE knockdown in zebrafish, however, only reduced but did not eliminate ribbons, indicating a more ancillary role. Here, we show in mice that full deletion of RIBEYE abolishes all presynaptic ribbons in retina synapses. Using paired reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
235
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(262 citation statements)
references
References 62 publications
23
235
4
Order By: Relevance
“…It is noteworthy that some of the features we report here differ from those found in a recent report characterizing retinal ribbons in Ribeye knockout mice (Maxeiner et al, 2016). In that study, the authors found ribbons completely lacking from the retina and a general decrease in vesicles residing near active zones.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that some of the features we report here differ from those found in a recent report characterizing retinal ribbons in Ribeye knockout mice (Maxeiner et al, 2016). In that study, the authors found ribbons completely lacking from the retina and a general decrease in vesicles residing near active zones.…”
Section: Discussioncontrasting
confidence: 99%
“…Morpholino oligonucleotide (MO) driven knock-down of ribeye leads to loss of calcium channel clusters in both retina (Lv et al, 2012) and neuromast hair cells (Sheets et al, 2012), whereas animals overexpressing Ribeye exhibit ectopic calcium channel clusters that colocalize with Ribeye protein aggregates (Sheets et al, 2012). More recently, knockout of Ribeye in mouse was found to cause a subtle change in the size of calcium channel clusters in photoreceptors (Maxeiner et al, 2016). Notably, in contrast to the previous MO results in retina (Lv et al, 2012), calcium channels remained clustered in discrete locations in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are thought to store a ready-releasable pool of synaptic vesicles and coordinate synchronous vesiclerelease at the synapse (Khimich et al, 2005;Buran et al, 2010;Matthews and Fuchs, 2010;Maxeiner et al, 2016). Voltage gated Ltype Ca 2+ channels are found to drive exocytosis at ribbon synapses and are localized at the base of ribbons (Platzer et al, 2000;Brandt et al, 2003;Dou et al, 2004;Sidi et al, 2004;Sheets et al, 2012;Wong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish larvae in which ribeye b, a gene coding for a major scaffolding protein in synaptic ribbons (Schmitz et al, 2000;Zenisek et al, 2004;Wan et al, 2005;Magupalli et al, 2008), is knocked down show reduction in the number of spikes of afferent neurons of the lateral line mechanosensory hair cells when the hair cells are stimulated (Sheets et al, 2011). Similarly, knockout mice for the ribeye gene (also known as Ctbp2) show impaired neurotransmitter release at retinal bipolar cells (Maxeiner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%